2016
DOI: 10.1080/20550340.2016.1253968
|View full text |Cite
|
Sign up to set email alerts
|

Zero-flow: a novel approach to continuous ultrasonic welding of CF/PPS thermoplastic composite plates

Abstract: Continuous ultrasonic welding of plastic films, fabrics, and even thermoplastic composite prepreg tape is a common industrial practice. However, continuous ultrasonic welding of stiff thermoplastic composite plates is challenging due to squeeze flow of resin at the welding interface, and significant local deformation of the welding stack, that are generally needed to achieve strong welds. This paper presents a novel approach to continuous ultrasonic welding of thermoplastic composite plates based on zero-flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 12 publications
2
37
0
Order By: Relevance
“…Similar studies were carried out by Senders et al [95] and Palardy et al [73,96] A comparison of flat energy director (PPS) and triangular energy director was also studied by Villegas et al, where CF/PPS composite was used [97]. In this investigation, they showed that the ED configuration with triangular strips has two more additional stages as compared to the conventional five stages in the flat ED study.…”
supporting
confidence: 68%
See 2 more Smart Citations
“…Similar studies were carried out by Senders et al [95] and Palardy et al [73,96] A comparison of flat energy director (PPS) and triangular energy director was also studied by Villegas et al, where CF/PPS composite was used [97]. In this investigation, they showed that the ED configuration with triangular strips has two more additional stages as compared to the conventional five stages in the flat ED study.…”
supporting
confidence: 68%
“…Similar studies were carried out by Senders et al [95] and Palardy et al [73,96] on the effect of flat energy directors, and using the displacement control mode with different material systems. CF/PPS and CF/PEI composites were used for the investigation, respectively.…”
supporting
confidence: 57%
See 1 more Smart Citation
“…[14][15][16] Continuous ultrasonic welding (CUW) has been shown to be a fast and feasible welding technique. 17 Senders et al demonstrated the feasibility of CUW by joining 100-mm-long carbon fiber-reinforced polyphenylene sulfide (CF/PPS) plates with a continuously welded seam. A thin (0.08 mm thick) PPS film energy director was used to minimize squeeze flow at the weld interface (''zero-flow'' welding).…”
Section: Introductionmentioning
confidence: 99%
“…Especially the field of joining and welding of thermoplastic composites has been studies extensively with a broad comprehensive knowledge base available. [1][2][3][4][5][6][7][8][9][10] Advanced manufacturing techniques have been discussed and demonstrated. [11][12][13][14][15] The so-called TAPAS (Thermoplastic Affordable Primary Aircraft Structure) consortium has demonstrated a number of large-scale thermoplastic components for aerospace applications since its launch in 2009.…”
Section: Introductionmentioning
confidence: 99%